Bilateral accessory heads of biceps brachii muscle coexisting with brachioradial artery passing between two layers of atypical bicipital aponeurosis - Ming Zhou; Akimitsu Ishizawa; Hideo Akashi; Ryoji Suzuki; Yoshio Bando (Elsevier, 2021)
Purpose: Although variations of biceps brachii muscle (BBM) and arm arteries are common, however, combined bilateral variations involving muscles and arteries are rarely described. The report's aim was the detailed presentation of a case of bilateral multiple anatomical variations in the upper extremities encountered during the dissection of a 90-year-old Japanese female cadaver. Results: On the left side, a third (accessory) head of the (BBM) was observed. Interestingly, the bicipital aponeurosis was composed of two layers, a superficial layer and a deep one. Arterial variations involved the high division of the brachial artery into the brachioradial artery (BRA), running superficially to the median nerve and the ulno-interosseous trunk occupying a normal position of the typical brachial artery. On the right side, a four-headed BBM was observed. The bicipital aponeurosis was also composed of two layers (superficial and deep), similarly to the left side. On this side, the BRA took origin from the axillary artery and crossed over the median nerve's medial root. Then, the BRA descended along the median nerve. On both sides, the BRA passed between two layers of the bicipital aponeurosis and continued its course in the forearm as the radial artery. Conclusions: Knowledge about the co-existence of multiple variations on the arm is essential for clinicians performing surgical procedures, and for medical education.